Pengaruh Perceived Usefulness, Perceived Ease of Use dan Promosi Penjualan melalui Mediasi Attitude Toward Using dan Perceived Security terhadap Behavioral Intention to Use (Studi Empiris: Pengguna Mobile Wallet di Jakarta) - Erickh Martua Sinurat; Liem Bambang Sugiyanto (Universitas Bunda Mulia, 2022)
The purpose of this study is to analyze the effect of sales promotion(SP), perceived usefulness(PU), perceived ease of use(PEU), perceived security(PS), and attitude toward using(ATU) towards behavioral intention to use(BIU) among mobile wallet users in Jakarta. This study uses a quantitative approach and uses structural equation models. In this study using 225 respondents with the provisions of mobile wallet users who live in Jakarta or in their daily activities in Jakarta. The data obtained were analyzed using the Structural Equation Model using AMOS. The results of this study indicate that PU, PEU has a fairly strong influence on ATU, then ATU also has a positive and significant effect on BIU. Furthermore, it has been found that ATU can mediate PU and PEU on BIU. Next, SP is the only independent variable that directly has a positive and significant influence on BIU. Through the results of this study also shows that sales promotion provides the largest contribution to behavioral intention to use, that mobile wallet users are happy with the sales promotion factor on the mobile wallet. Furthermore, based on the results of this study it also shows that perceived usefulness, perceived ease of use, and perceived security have no direct influence on behavioral intention to use. The limitations in this study are the use of mobile wallets which are used as respondents who live in Jakarta or have daily activities in Jakarta and the limited number of research objects. The implication of this research is to provide recommendations that mobile wallet service providers can increase behavioral intention to use on mobile wallets by increasing and implementing the right strategy on sales promotion, then through attitude toward using can also increase behavioral intention to use on mobile wallets, namely by paying attention to the features of the mobile wallet service that are easily understood by users.